Exploring the neighbourhood physical environment's role on the walking experience of people living with dementia and mild cognitive impairment - Habib Chaudhury; Joey Oi Yee Wong; Daizi Davies; Lillian Hung; Shannon Freeman; Mark Groulx; Kishore Seetharaman; Cari Randa-Beaulieu; Mario Gregorio (SSM: Qualitative Research in Health, 2025)
The number of persons living with dementia is increasing globally, and many of whom live in community settings. The neighbourhood environment has an important role in supporting persons living with dementia in accessing amenities and services, as well as fostering social participation. Despite the growing recognition of the importance of dementia-inclusive neighbourhoods, there is limited evidence on the influence of the physical environment on the mobility and community participation of persons living with dementia. Based on the theoretical underpinnings of environmental gerontology and a strength-based approach, this study contributes to understanding the neighbourhood physical environment's role in the walking experiences of persons living with dementia. The study was conducted with 32 older adults living with dementia and partners in Metro Vancouver and Prince George, British Columbia, Canada. This paper presents findings based on the 26 participants in Metro Vancouver. Each participant (or dyad) took part in four sessions involving various data collection methods: a structured questionnaire, semi-structured sit-down and walk-along interviews, and photo and video documentation. Through reflexive thematic analysis, five themes were generated: 1) Staying on track, 2) Sensory experiences, 3) Nature matters, 4) Benefits and challenges of construction work and 5) Walking indoors. The findings from this study contribute to the evidence base on the neighbourhood's role in supporting independence and participation of persons living with dementia, which can inform city planners, developers and urban designers on city planning and design, and provide insights for future research in this area.